2008
DOI: 10.1021/om800170x
|View full text |Cite
|
Sign up to set email alerts
|

Rare-Earth-Metal Mixed Hydride/Aryloxide Complexes Bearing Mono(cyclopentadienyl) Ligands. Synthesis, CO2 Fixation, and Catalysis on Copolymerization of CO2 with Cyclohexene Oxide

Abstract: Hydrogenolysis of mono(cyclopentadienyl)-ligated rare-earth-metal bis(alkyl) complexes Cp′Ln(CH2SiMe3)2(THF) (Ln = Y (1a), Dy (1b), Lu (1c); Cp′ = C5Me4SiMe3) with PhSiH3 afforded the mixed hydride/alkyl complexes [Cp′Ln(μ-H)(CH2SiMe3)(THF)]2 (Ln = Y (2a), Dy (2b), Lu (2c)). The overall structure of complexes 2a−c is a C 2-symmetric dimer containing a planar symmetric Ln2H2 core at the center of the molecule. Deprotonation of ArOH (Ar = C6H2- t Bu2-2,6-Me-4) by the metal alkyl group of 2a−c led to formation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 87 publications
5
48
0
1
Order By: Relevance
“…Several efficient catalyst systems, such as zinc, aluminum, cadmium, manganese, cobalt, chromium, and rare-earth-metal complexes, in combination with other reagents for the copolymerization of CO 2 and alicyclic epoxides such as propylene oxide have been developed. [3][4][5][6][7] Recently, salentype catalysts have become the focus of many groups. The chemical structures of the complexes as catalysts are related to the overall catalytic copolymerization performance of CO 2 with an epoxide.…”
Section: Introductionmentioning
confidence: 99%
“…Several efficient catalyst systems, such as zinc, aluminum, cadmium, manganese, cobalt, chromium, and rare-earth-metal complexes, in combination with other reagents for the copolymerization of CO 2 and alicyclic epoxides such as propylene oxide have been developed. [3][4][5][6][7] Recently, salentype catalysts have become the focus of many groups. The chemical structures of the complexes as catalysts are related to the overall catalytic copolymerization performance of CO 2 with an epoxide.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 Bond lengths (Å) and angles (deg) for complexes 1. The absorption at ca 1565 cm À1 in the IR spectra of complexes 4-Yb and 4-Er may be assigned to the carbonate group [51]. The structures of 4 are shown in Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Subsequently, research has focussed on well-defined singlesite catalysts of the stoichiometry (LMX), where L is an ancillary ligand, M is the Lewis acidic metal centre and X is the co-ligand or initiating group. Metal centres (M) with a strong precedent in this field include Zn(II), Co(III) and Cr(III), although successful complexes of metals including Ti(IV) [50,51], Zr(IV) [50], Sn(IV) [50], Ge(IV) [50], Mn(II) [52], Mn(III) [52][53][54], Fe(III) [55,56], Lu(III) [57], Y(III) [57,58], Sc(III) [58], Dy(III) [57,58], Lu(III) [57,58], Al(III) [59][60][61][62], Mg(II) [63,64], Co(II) [38,65], Cu(II) [66] and Ni(II) [67] have all been reported and will be highlighted herein. Whilst a range of ancillary ligands (L) have been explored and will be the described in more detail subsequently, it is possible to identify some common and successful ligand classes (Fig.…”
Section: Catalyst Classes and Scope Of The Reviewmentioning
confidence: 99%
“…In 2005, a series of dimeric rare-earth metal complexes for CHO/CO 2 copolymerisation were reported [57,58]. Hou and co-workers showed that halfsandwich bis(alkyl) lutetium complexes underwent CO 2 insertion leading to dimeric compounds, as depicted in Fig.…”
Section: Dimeric and Multimeric Structures (Iib)mentioning
confidence: 99%